Interactive Multimedia Development Using Flash Completed Quizmaker on Structural Materials and Plant Tissue Functions for SMP Students - Chairatun Dyna; Rahmawati D; Mades Fifendy (ATRIUM PENDIDIKAN BIOLOGI, 2016)
Teaching media is helping equipment of teaching material, so the result can motivate the students, but the teachers generally dont use any interesting media, they still use the media that they get in the school like chart, torso, text book, and power point slide that all the medias dont use effective. The multimedia will be effective and interesting when they get correlation between user and interactive multimedia namely flash that completely by a quizmaker to the structure and function of plant network for junior high school students that valid and practice.This research used athree-stage development of 4-D models consisted of steps which were define, design, and development, while disseminate stage was not performed because of time constraints. Subjects of this study consisted of one lecturer of biology at FMIPA UNP, two teachers of SMPN 2 Padang Panjang, and 20 students of class VIII SMPN 2 Padang Panjang. Research data was primary data that obtained through validity and practicality questionnaire, then analyzed with descriptive analysis. Based on data analysis, it was obtained that validity value by validator was 97.99% (valid), practicality value by teachers was 88.74% (practical) and practicality value by students was 85.19% (practical). Based on this, we can conclude that flash interactive multimedia that equipped with quiz-maker that being produced in this research for material structure and function of plant tissue subject for junior high school students are valid and practical.